Comparison Between E-Learning and M-Learning Using Learning Outcome and IPA Matrix - Rufman Akbar (Universitas Pendidikan Ganesha, 2025)
The integration of technology in higher education has positioned e-learning and m-learning as primary modes of instruction. However, their effectiveness in supporting student achievement and satisfaction has rarely been compared comprehensively. This study compares e-learning and m-learning by analyzing student learning outcomes and perceptions using the Importance-Performance Analysis (IPA) Matrix. The sample consisted of two classes enrolled in the same course, each using either e-learning or m-learning. Assessment scores were used to measure academic performance, while a perception questionnaire was analyzed through IPA to map the strengths and weaknesses of each platform. The results show that students in the m-learning group achieved higher academic outcomes and reported more positive perceptions, particularly in content quality, technical reliability, and ease of use. In contrast, the e-learning group demonstrated weaknesses in technical and user experience aspects. Overall, the study concludes that m-learning is more effective and satisfying, offering greater potential to support digital learning—especially for digital-native students in higher education context.